Migration, development and remittances in Europe : mixed impacts and the role of institutions - Peixoto, João (2010)
In this paper, the specific role of remittances in the migration-development nexus will be examined. It will be argued that migrants’ remittances exert mixed impacts (positive, negative and neutral) over the economic development of sending countries, and that institutions play a crucial role in maximizing the positive and minimizing the negative ones. The main geographical area taken into consideration is Europe, one of the most important world regions in the volume of international migration, and particularly Central and Eastern Europe, a crossroad for many inward and outward flows, and also a fast-growing beneficiary of immigrants’ remittances. In the first section, some trends of current international migration in Europe will be highlighted, including flows involving Central and Eastern Europe, as well as some causal factors and prospects for continuing migration in the future. In the second section, remittances will be observed as one of the main consequences of international migration, and an evaluation of its volume in Central and Eastern European (and Central Asian) economies will be done. In the third section, impacts of remittances over development will be stressed, revealing its mixed effects (positive, negative and neutral). Finally, the specific role of economic, social and political institutions will be discussed, arguing that they exert a vital role in determining which outcomes will predominate